2020
DOI: 10.1186/s40795-020-00398-9
|View full text |Cite
|
Sign up to set email alerts
|

Increasing levels of Parasutterella in the gut microbiome correlate with improving low-density lipoprotein levels in healthy adults consuming resistant potato starch during a randomised trial

Abstract: Background Prebiotics, defined as a substrate that is selectively utilized by host microorganisms conferring a health benefit, present a potential option to optimize gut microbiome health. Elucidating the relationship between specific intestinal bacteria, prebiotic intake, and the health of the host remains a primary microbiome research goal. Objective To assess the correlations between gut microbiota, serum health parameters, and prebiotic consumption in healthy adults. Methods We performed ad hoc explorato… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…RPS consumers had a gut microbiome containing higher Parasutterella (phylum Proteobacteria ) levels than subjects consuming placebo, andsuch increases were correlated with reductions in the blood levels of low-density lipoproteins. On this basis, it is feasible that the effect of Parasutterella on the host’s metabolism might depend upon several partly unknown factors, including prebiotic consumption, and they could play a critical role in cholesterol homeostasis [ 68 , 69 ].…”
Section: Resistant Starch In Human Nutritional Intervention Studies: Gi and Impact On Inflammation And Gut Microbiomementioning
confidence: 99%
See 2 more Smart Citations
“…RPS consumers had a gut microbiome containing higher Parasutterella (phylum Proteobacteria ) levels than subjects consuming placebo, andsuch increases were correlated with reductions in the blood levels of low-density lipoproteins. On this basis, it is feasible that the effect of Parasutterella on the host’s metabolism might depend upon several partly unknown factors, including prebiotic consumption, and they could play a critical role in cholesterol homeostasis [ 68 , 69 ].…”
Section: Resistant Starch In Human Nutritional Intervention Studies: Gi and Impact On Inflammation And Gut Microbiomementioning
confidence: 99%
“…The beneficial effect of a long-term (12 months) dietary intervention with increased fiber intake, including RS on humans, was assessed [ 69 , 70 ]. In the study, two dietary groups were investigated, RS group subjects ingested higher amounts of food rich in RS (especially cereals and legumes) in order to consume about 15 g/day of RS, while subjects in the fiber group received general advice to ingest vegetables rich in fiber, without specific advice on the intake of RS-rich foods.…”
Section: Resistant Starch In Human Nutritional Intervention Studies: Gi and Impact On Inflammation And Gut Microbiomementioning
confidence: 99%
See 1 more Smart Citation
“…A decrease in Parasutterella would be detrimental to DM subjects because Parasutterella has been correlated with reductions in low-density lipoprotein levels. 48 Further, Coriabacteriaceae ; g _UCG-003 was the only genus that increased in both DM1 and DM2 microbiomes, and four other genera ( Phascolarctobacterium, Lachnospiraceae, Megasphaera , and Romboutsia ) that are either probiotic or anti-inflammatory in function increased only in DM2 microbiomes. 42 , 43 …”
Section: Discussionmentioning
confidence: 92%
“…Baxter et al [ 18 ] reported increased fecal butyrate levels detected at a 14 g/day dose level for potato starch, though did not report on microbiota changes at this dose level. Furthermore, isolated prebiotic potato starch has been shown to significantly increase levels of Bifidobacterium [ 54 , 55 ], one of the most commonly reported effects of potato starch consumption on the gut microbiota [ 56 ]. In unpublished results, the same group has seen Bifidobacterium increases in doses as low as 3.5 g/day.…”
Section: Discussionmentioning
confidence: 99%